2020
DOI: 10.3390/nano10030446
|View full text |Cite
|
Sign up to set email alerts
|

A First-Principles Study of Nonlinear Elastic Behavior and Anisotropic Electronic Properties of Two-Dimensional HfS2

Abstract: We utilize first principles calculations to investigate the mechanical properties and strain-dependent electronic band structure of the hexagonal phase of two dimensional (2D) HfS2. We apply three different deformation modes within −10% to 30% range of two uniaxial (D1, D2) and one biaxial (D3) strains along x, y, and x-y directions, respectively. The harmonic regions are identified in each deformation mode. The ultimate stress for D1, D2, and D3 deformations is obtained as 0.037, 0.038 and 0.044 (eV/Ang3), re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 44 publications
2
4
0
Order By: Relevance
“…The rectangular supercells of the HfS 2 and SiSe monolayers were used to investigate the anisotropic performance. The presently optimized lattice constants of the HfS 2 monolayer (a = 6.21, b = 3.59 Å) and the SiSe monolayer (a = 5.98, b = 3.47 Å) are consistent with those that had been previously reported, [37][38][39]42,43,54 shown in Table S1 (ESI †). Therefore, the mismatch ratio of the HfS 2 and SiSe heterostructures is approximately 4%.…”
Section: Geometrical Structures Of the Monolayers And Heterostructuressupporting
confidence: 88%
See 1 more Smart Citation
“…The rectangular supercells of the HfS 2 and SiSe monolayers were used to investigate the anisotropic performance. The presently optimized lattice constants of the HfS 2 monolayer (a = 6.21, b = 3.59 Å) and the SiSe monolayer (a = 5.98, b = 3.47 Å) are consistent with those that had been previously reported, [37][38][39]42,43,54 shown in Table S1 (ESI †). Therefore, the mismatch ratio of the HfS 2 and SiSe heterostructures is approximately 4%.…”
Section: Geometrical Structures Of the Monolayers And Heterostructuressupporting
confidence: 88%
“…The anisotropic electronic properties and nonlinear elastic behavior of the HfS 2 monolayer were explored using the first-principle calculations. 37 The effects of the vertical strain on the electronic and optical properties were investigated by Hoat et al 38 The enhanced effects of the intrinsic structural defects on the thermoelectric and optoelectronic properties are also reported for the HfS 2 monolayer. 39 Opoku et al 40 reported that the conduction band minimum (CBM) of HfS 2 matches the reduction potential for H + /H, but Wang et al 41 gave the opposite conclusion.…”
Section: Introductionmentioning
confidence: 96%
“…Table shows the stable crystal structure of monolayer HfS 2 , which can be observed to be in good agreement with the theoretical results in previous reports in the literature , and proves the reliability of our calculations. Furthermore, the stability of the structure is verified by calculating the phonon dispersion without an imaginary frequency (Figure a).…”
Section: Resultssupporting
confidence: 90%
“…142 HfS 2 nanosheets can withstand large ultimate strains in D1, D2 and D3 (that is, the three directions of x, y, and x-y). 143 The other materials in the TMD family, such as WS 2 , NiTe 2 , MoSe 2 , WSe 2 etc., are also known for their high mechanical stability. 141 All of this indicates the great potential of strain engineering to regulate the HER activities of TMDs.…”
Section: Strain Engineeringmentioning
confidence: 99%